Theoretical and Practical Criteria Orienting the use of Mobile Devices in Family Communication with Teens - Gómez Ibañez, Janett Melita (2019)
On the basis of the current context of use of mobile devices by adolescents, the need arises to establish the theoretical and practical criteria to promote family communication based on this reality. From a quantitative, descriptive and interpretive study, theories were identified that support the insertion of these devices as well as those that describe their use as objects of conflict and family intrusion.It was concluded that, in the early adolescent stage there is a moderate extension of use that increases progressively with age, and the need to design proposals that guide families about the advantages and risks that the use of these devices generate.